Factors influencing the implementation of a teacher professional development program to improve teaching quality - Silva Didier, Lucas; Schildkamp, Kim; Visscher, Adrie J.; Bosker, Roel J. (Frontiers in Education, 2025)
In this study, we examined why a Teacher Professional Development (TPD) program, designed to support teachers in using students’ perceptions of teaching quality (SPTQ) data, faced significant implementation challenges in 17 secondary schools in Chile. Despite voluntary participation and initial interest, 15 of the 17 schools dropped out within 2–3 months of starting the program. Through 12 semi-structured interviews with professional learning community coordinators from nine schools, we investigated four key attributes of the TPD program to understand implementation challenges: its added value, compatibility, clarity, and tolerance. While coordinators valued several aspects of the program (including its structured manual, evidence-based teaching strategies, and integration of SPTQ data) significant implementation barriers emerged. Time constraints, lack of technological infrastructure, and insufficient organizational routines made the implementation of the TPD program too burdensome for most schools. We discuss how compatibility between TPD programs and schools’ existing structures and routines acts as a critical bottleneck that can prevent successful implementation, even when participants see value in the program. This study provides important insights into the conditions necessary for successful TPD implementation in a global south country.